STUDIES ON NORTH WEST INDIAN AGARICS: THE GENUS LACTARIVS - D. K. MANN, N. S. ATRI, S. S. SAINI AND (Indian Phytopathology, 2002)
Four taxa of the genus Lactarius Pers. (L serifluus) (Fr.) Fr., L subvernalis var. albo-ochraceus Hesler & Smith, L proximellus Beardslee & Burlingham and L cillardii Coker) collected from North-Western Himalayas are illustrated and described for the first time from India.